Pemasaran Terhadap Usaha Makro Kecil (UMKM ) Terhadap Penjualan Ketoprak Di Daerah Padang Serai Kota Bengkulu - Putri, Jessica Nadia; Febliansa, M. Rahman; Gayatri, Ida Ayu Made Er Meytha; Irwanto, Tito (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
This study explores the role of marketing strategies in enhancing the sales performance of traditional culinary products, specifically *ketoprak*, among Micro, Small, and Medium Enterprises (MSMEs) in the Padang Serai area of Bengkulu City. MSMEs play a crucial role in the regional economy by creating employment opportunities and supporting local economic growth. However, these businesses often face significant challenges in marketing, particularly amid increasing competition. Therefore, this research aims to assess the extent to which marketing strategies implemented by ketoprak vendors influence their sales outcomes.